Reviewing the Development and Adaptation Steps of the Scales Specifically Used for Pregnancy, Childbirth, and Postpartum in Türkiye Between 2010 and 2020. - Kahraman, Ayşenur; Altınayak, Serap Öztürk; Eroğlu, Vasviye; Alatlı, Betül (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2023)
Background: Scales are widely used in scientific research. In Türkiye, many scales are used in midwifery. However, there is no standard approach to scale development and adaptation. To clarify this situation, it is extremely important to study the steps of scale development and adaptation. Aim: The aim of this study is to investigate the steps of scale development and adaptation used in pregnancy, childbirth, and postpartum. Methods: The study was conducted in a retrospective and descriptive design. The study population consists of scale studies specifically related to pregnancy, childbirth, and postpartum in Türkiye published between 2010 and 2020. The sample consisted of 14 scale development studies and 31 scale adaptation studies retrieved from the ULAKBIM-TR (Turkish Academic Network and Information Centre), Google Academic, and Higher Education Council National Thesis Centre Database (n = 45). In examining the studies, content analysis was conducted using the "Scale Development Process Control Form" and the "Scale Adaptation Process Control Form," which were prepared in accordance with the literature. The frequency and percentage distributions of the data were analyzed using the Statistical Package for Social Sciences 26 package program. Results: The theoretical basis of the measured structure and the purpose of the measurement instrument are stated in all articles. Exploratory factor analysis and confirmatory factor analysis were used together to determine construct validity in 57.1% of the developed scales and 54.8% of the adapted scales. No pilot study was conducted in 29% of the scale adaptation studies and in 21.4% of the developed scales. The Cronbach's alpha coefficient was calculated to estimate the reliability of almost all the scales studied. Conclusion: The analysis of the data obtained shows that the opinions of the measurement and evaluation experts were not taken into account and the pilot study application was not used in the studies examined. To avoid errors in this area and to perform the process correctly, it is recommended to develop guidelines and create up-to-date resources and algorithms.